Semicircular slot based UWB microstrip patch antenna for variable band notched applications - Hasan Mahfuz, M M; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Abdul Malek, Norun Farihah (Penerbit UTM Press, 2022)
The patch antenna with Ultra-Wide Band (UWB) characteristics is a promising candidate for wireless communication. It is a major research problem to mitigate electromagnetic interference (EMI) with narrowband technologies such as 5G lower band, Wi-MAX, WLAN and satellite band, which are all in the UWB region. This study describes a UWB antenna with variable band rejection that can be used to avoid interference with Wi-MAX and 5G lower band applications. The UWB characteristics of a simple rectangle patch antenna with a faulty ground structure has been designed for operational bandwidth (2.7–13) GHz. A novel method semicircular slot (SCS) at the radiation patch creates a band notched from (3.25–3.80) GHz and (3.4–4) GHz. Variable band rejection between (2.95–4.40) GHz can be achieved by adjusting the “Wa” values. When measured over the band rejection frequency, the return loss (S11) and VSWR values are very close to 0 dB and larger than 2. The simulated and measured results such as return loss, VSWR, 2-D polar pattern and gain have almost similar agreement. The design of the suggested antenna is simple, compact and efficient for Wi-MAX application, this is an ideal UWB antenna with the band notch characteristics.